Filterability of staphylococcal species through membrane filters following application of stressors - Onyango, Laura A (BioMed Central, 2010)
BACKGROUND: Passage of bacterial cells through filter pores has been reported for a number of bacterial species. In this investigation, we tested the filterability of staphylococcal cultures that were exposed to several environmental stress conditions by passing them through 0.22 and 0.45 μm sterile filters, which are industry standards. FINDINGS: Results showed repeated passage of viable staphylococcal cells through both pore sizes, although more passage was seen through the 0.45 μm pore size. Of the three staphylococcal species, S. lugdunensis showed the best passage at relatively higher numbers regardless of the treatment, while both S. aureus and S. epidermidis showed limited passage or complete inhibition. CONCLUSION: The data showed that staphylococcal bacteria were capable of passing through sterile filters in a viable state. There was better passage through 0.45 μm sterile filters than through the 0.22 μm sterile filters. Application of a stress condition did not appear to enhance filterability of these bacterial cultures.